2010
DOI: 10.1103/physrevb.81.104514
|View full text |Cite
|
Sign up to set email alerts
|

Spectral properties of a resonator driven by a superconducting single-electron transistor

Abstract: We analyze the spectral properties of a resonator coupled to a superconducting single-electron transistor ͑SSET͒ close to the Josephson quasiparticle resonance. Focusing on the regime where the resonator is driven into a limit-cycle state by the SSET, we investigate the behavior of the resonator linewidth and the energy relaxation rate which control the widths of the main features in the resonator spectra. We find that the linewidth becomes very narrow in the limit-cycle regime, where it is dominated by a slow… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…30,[47][48][49][50][51][52][53][54][55][56][57][58][59][60] Due to the many oscillator states participating in transport the matrix representations of the involved operators are of large dimensions and it is necessary to resort to numerics. We demonstrate the numerical stability of our recursive algorithm up to very high cumulant orders (∼ 100) and show how oscillations of the cumulants can be used to extract information about the analytic structure of the cumulant generating function.…”
Section: Introductionmentioning
confidence: 99%
“…30,[47][48][49][50][51][52][53][54][55][56][57][58][59][60] Due to the many oscillator states participating in transport the matrix representations of the involved operators are of large dimensions and it is necessary to resort to numerics. We demonstrate the numerical stability of our recursive algorithm up to very high cumulant orders (∼ 100) and show how oscillations of the cumulants can be used to extract information about the analytic structure of the cumulant generating function.…”
Section: Introductionmentioning
confidence: 99%
“…This includes systems in some general mixed states and in particular in thermal states. In this respect, we hope that the present method could be beneficial in various experimental systems, such as nanoelectromechanical systems (NEMS) [15,16] and mesoscopic systems.…”
Section: Discussionmentioning
confidence: 98%
“…where f abc and g abc determine the structure of the basis. Substituting equation (14)- (16) in equation (13) we obtain…”
Section: Constructing the Dynamics For Discrete Systemsmentioning
confidence: 99%
“…55 Many groups focused their attention on this regime, employing rate equations to study transport phenomena such as the Franck-Condon blockade, super-Poissonian shot noise, 9,10,12,24 and even peculiar effects such as subPoissonian out-of-equilibrium vibron distributions. 28,29,33,56,57 In the opposite regime of slow vibrations γ 1, electrons are extremely sensitive to the position of the oscillator, which can be treated in a semiclassical approximation. 26,30,31,58 Indeed, Mozyrsky et al have shown 25 that it is the onset of a semiclassical Langevin dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…23 A great variety of NEMS setups have been investigated theoretically. Typically, the electronic part is composed of a semiconducting, [24][25][26][27][28][29] normal, [30][31][32] or superconducting [33][34][35][36] single quantum dot. 37 Double-dot setups have been studied as well.…”
Section: Introductionmentioning
confidence: 99%